2013
DOI: 10.1136/bmjspcare-2012-000380
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between depression and physical symptom burden in advanced cancer

Abstract: These findings support the view that a synergistic relationship exists between depression and a broad array of physical symptoms in patients with advanced cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 39 publications
3
82
1
2
Order By: Relevance
“…We have demonstrated in metastatic cancer that depression represents a final common pathway of distress related to burden of disease and to such individual factors such as self‐esteem, the sense of meaning, and attachment security . Depressive symptoms in the present study were associated with a greater number of physical symptoms and distress about these symptoms, and with lower spiritual meaning and peace, similar to findings in patients with metastatic cancer . We have also shown that depression contributes to the amplification of somatic symptoms .…”
Section: Discussionsupporting
confidence: 84%
“…We have demonstrated in metastatic cancer that depression represents a final common pathway of distress related to burden of disease and to such individual factors such as self‐esteem, the sense of meaning, and attachment security . Depressive symptoms in the present study were associated with a greater number of physical symptoms and distress about these symptoms, and with lower spiritual meaning and peace, similar to findings in patients with metastatic cancer . We have also shown that depression contributes to the amplification of somatic symptoms .…”
Section: Discussionsupporting
confidence: 84%
“…Cross-sectional research has consistently found that many factors including greater depression [15], anxiety [17], distress [18], and lower quality of life [19] are correlated with greater pain levels among cancer patients. Cross-sectional research has consistently found that many factors including greater depression [15], anxiety [17], distress [18], and lower quality of life [19] are correlated with greater pain levels among cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…Depressive disorders in the context of cancer can have clinically relevant effects on health outcomes. Depression has been associated with more prolonged hospital stays, increased physical distress, poorer treatment compliance, lower quality of life, and increased desire for hastened death . More severe depression in cancer has also been shown to be a risk factor for death, independent of medical variables .…”
Section: Introductionmentioning
confidence: 99%